2015
DOI: 10.1111/pme.12710
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency of Dorsal Root Ganglia for the Treatment of Complex Regional Pain Syndrome in an Adolescent with Poliomyelitis Sequel: A Case Report

Abstract: This case illustrates that PRF applied to lumbar 4 and lumbar 5 DRG may play a significant role in CRPS type 1 management after the surgical treatment of poliomyelitis sequelae in adolescent patients. Further randomized, controlled studies are needed to support this argument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Traditionally, the DRG neuron is considered to be a structure that merely ‘supports’ physiological communication between the peripheral and central nervous systems to convey peripherally encoded information to the spinal cord or trigeminal nuclei of the brain stem. 15 However, new clinical data have shown that a pulsed radiofrequency current applied to the DRG may reduce pain intensity in patients with complex regional pain syndrome 16 or lumbosacral radicular syndrome. 17 Thus, the DRG is an active participant in the processing of pain information and therefore a robust target for neuromodulation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the DRG neuron is considered to be a structure that merely ‘supports’ physiological communication between the peripheral and central nervous systems to convey peripherally encoded information to the spinal cord or trigeminal nuclei of the brain stem. 15 However, new clinical data have shown that a pulsed radiofrequency current applied to the DRG may reduce pain intensity in patients with complex regional pain syndrome 16 or lumbosacral radicular syndrome. 17 Thus, the DRG is an active participant in the processing of pain information and therefore a robust target for neuromodulation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Both RCTs included participants with low back pain (LBP) [14,15]. Non-randomized studies included patients with the following indications: LBP [16][17][18], postsurgical pain [19][20][21], pain associated with herpes zoster [6], cervicogenic headache [22,23], complex regional pain syndrome type 1 [24,25], intractable vertebral metastatic pain [26], chronic scrotal and inguinal pain [27], occipital radiating pain in rheumatoid arthritis [28] and chronic migraine [29] (Table 1). These studies had highly heterogeneous parameters of stimulation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This group included only two case reports [24,25] with three participants included. Albayrak et al [24] reported cases of two women with post-stroke complex regional pain syndrome (CRPS).…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…35 Dermatomes responsible for generating pain are also inhibited by the application of PRF to the DRG in disorders associated with neuropathic pain, such as cervical or lumbar radicular pain, postherpetic neuralgia, and complex regional pain syndrome. 36,37 The primary nerve innervation of the knee arises from the femoral nerve (originates from branches of L2-L4 dorsal rood) and from the sciatic nerve (originates from branches of L4, L5, sacral [S] 1, S2, S3 nerves). 38,39 In previous case reports, RF application was effective in reducing PPSP after TKA when applied to the peripheral branch of the sciatic 18,19 or femoral nerve.…”
Section: Discussionmentioning
confidence: 99%